The Effect of Using Plotagon Learning Media on Students' Learning Outcomes in Aqidah Akhlak for VIII Grade Students at MTsN 4 Madiun - Sinta Syarif; Halida Umami (Universitas Islam Lamongan, 2026)
Initial observations at MTsN 4 Madiun revealed that the learning outcomes of eighth-grade students in Aqidah Akhlak were relatively low, as many students had not achieved the Minimum Mastery Criteria (KKM) of 70. This condition was influenced by the limited use of varied instructional media, indicating the need for more innovative learning tools. This study aims to examine the effect of using Plotagon as a learning medium on students' learning outcomes. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The sample consisted of two classes: VIII B as the experimental group and VIII C as the control group, each with 30 students. The results showed that both groups had relatively equivalent initial abilities, with mean pretest scores of 71.33 (experimental) and 70.50 (control). After treatment, the experimental group showed significant improvement, with a mean posttest score of 85.67, higher than the control group's 71.33. Hypothesis testing showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, confirming a significant positive effect.